O processo de trabalho do enfermeiro em unidades pediátricas em um hospital de ensino: implantação de um programa educativo - Vieira, Maria Rita Rodrigues (2007)
In Brazil, the interest in the attention quality to the child s health has been taking as reference the high infant morbidity and mortality indexes along the times, and it has been counting on orientations from world and transnational official services, and propositions from national organizations. The intervention proposals include different health professionals on integrated participation, being respected their own professional specificities. Therefore, the General Objective of this study was to analyze the main aspects on nurses work process in pediatric units in a school hospital, interior of São Paulo state, to plan and introduce the consciousness education aiming at some reflexion of the reality of their own practice. This is descriptive study with quanti-qualitative approach developed into two moments: the descriptive analysis at the first moment; the analysis of Paulo Freire s generative theme for the development of the educational activity at the second. The ethical aspects of research with human beings were preserved as part of the study; 17 (73.9%) of the 23 nurses that have been performing in pediatric units in the morning, afternoon and night shifts participated in the study. At the first moment, the survey of thematic universe was made by means of a structured interview. It allowed to outline the profile and perceptions on the assistance that these nurses performed, observing that: 52.9% aged from 25 to 30 years; 76.5% have been graduated for 3 to 10 years; 94.1% have been performing for 3 to 27 years in the pediatric area; 58.8% had made some training in this area and 64.7% have chosen to work in Pediatrics. The obtained data on their perceptions for the management of the work process in the pediatric units, allowed the identification of generative themes for the educational actions that took place in four meetings with discussion circles; this was the second moment of the research. Four generative themes were identified: the interpersonal relationship in the work unit; the importance of including the child s growth and development in the nurse s care; the continuity of the treatment at home and management in Pediatrics. In the educational meeting, there was the understanding of how the nursing work process occurs in the pediatric units, and which solutions were more feasible for changes in this context, to improve the quality of this assistance. This has allowed to conclude that the strategies of the method applied were appropriate for the reflection regarding their difficulties in the work process as well as the possibility to use the generative content in the discussions for a transforming practice in pediatric nursing environment.